Social Media on the Students’ Academic Performance - Ashley Bridget Sophie V. Bedua; Charles Vincent P. Bengan; Erich P. Ea; Daven John G. Goleng; Ryan Gerome D. Posanso; Cheryl T. Pueblo; Hassanal P. Abusama (Universitas Pendidikan Indonesia (UPI), 2021)
This study aims to determine the impact of social media on students' academic performance in terms of their grade point average (GPA). This study specifically aimed: (1) to determine the percentage of students using social media in terms of doing research work, doing assignments or projects, and studying, (2) to find out the time students spend on social media, (3) to find out the academic performance of students in terms of GPA, (4) to determine if there is a significant relationship between time spent on social media and academic performance in terms of GPA, (5) to determine if there is a significant relationship between usage of social media and academic performance in terms of GPA. A quantitative approach was employed to support this study, particularly the correlation method was utilized. Survey questionnaires were used to solicit data and information from 35 randomly chosen respondents of the study. This study's findings revealed that 80% of students used social media in terms of doing research work, 90% in terms of doing assignments or projects, and 80% in terms of studying. Students' time spent on social media is 1-6 hours, and academic performance in terms of GPA is 90-93. It was also revealed that there is a significant relationship between time spent on social media and academic performance in terms of GPA and a significant relationship between usage of social media and academic performance in terms of GPA. This study can be a bridge for understanding the gap of lack of sufficient information on the effects of social media on high school student